Free trade federalism in the European Community and Australia - Townsend, DJ (2009)
Australia and the European Community confront similar problems in seeking to ensure economic mobility within a non-unitary system of government. Taking as its focus one notable impediment to economic mobility, this thesis compares the judicial interpretation of each system’s constitutional prohibition of non-fiscal impediments to the free movement of goods, paying particular attention to the implications which the jurisprudence on this subject has for the balance between economic integration and State regulatory autonomy in each system. Both Australian and EC law on this subject are broadly structured around the identification of relevant restrictions to the free movement of goods and, where such restrictions are discerned, the identification of valid justifications for such restrictions. A wide definition of relevant restrictions tends to promote economic integration, while a wide definition of valid justifications tends to preserve State regulatory autonomy. In relation to the definition of relevant restrictions, EC law displays a much greater inclination towards economic integration that Australian law. Under Australian law, the general test for relevant restrictions is whether the law in question imposes a discriminatory burden of a protectionist kind. In the EC, the test differs depending on the category of law under consideration, and although laws on selling arrangements may still only qualify as relevant restrictions if they have a discriminatory effect, recent case law has confirmed the re-emergence of the broader market access test for determining whether laws on the use of products qualify as relevant restrictions. Moreover, laws on product standards continue to qualify automatically as relevant restrictions, thus automatically requiring States to justify all such laws to the court’s satisfaction. Similarly, EC law displays a preference for economic integration in employing a comparatively strict definition of valid justifications. Australian law acknowledges any non-protectionist purpose as a legitimate purpose for justification and only requires that the State legislation be necessary to achieve that purpose. EC law, by contrast has a limited set of legitimate purposes of general application, and only acknowledges the legitimacy of other purposes where the law in question is non-discriminatory on its face. Additionally, EC law not only requires that the State law be necessary to achieve a legitimate purpose but may also go so far as to decide that a State law necessary for the achievement of a legitimate interest is nevertheless invalid because that purpose was not important enough to balance the burden which is placed on free movement of goods and economic integration. Perhaps surprisingly, then, on the present state of affairs Australian law displays a much more even-handed approach to the prohibition of non-fiscal impediments to trade and preserves a great degree of State autonomy, whereas EC law evinces a clear preference for economic integration and curtails State autonomy to a much greater degree.